Boosting I - Wang, Jun
Previous studies have shown that disk I/O times are one of the major performance bottlenecks of Internet servers such as proxy cache servers. Most conventional file systems do not work well for such systems because of their very high overheads. Although Special-purpose operating systems may achieve high performance, it is very difficult and expensive to design and maintain. They also have very poor portability. In this paper we propose to built user-space, customized file systems for Internet servers so as to achieve high-performance, low-implementation-cost and good portability at the same time. To provide an example of such systems, we presented a novel scheme called WPSFS that can drastically improve I/O performance of proxy servers and other applications. WPSFS is an application-level software component of a proxy server which manages data on a raw disk or disk partition. Since the entire system runs in the user space, it is easy and inexpensive to implement. It also has good portability and maintainability. With efficient in-memory meta-data data structures and a novel file system called Page-structured file system(PFS), WPSFS achieves 9-20 times better I/O performance than the state-of-the-art SQUID server running on a Unix Fast File System, and 4-10 times better than the improved SQUIDML.